Pengaruh Brand Ambassador dan Brand Awareness Terhadap Keputusan Pembelian yang Dimoderasi Brand Image (Studi Pada Konsumen Le Minerale di Toko Indomaret Soekarno Hatta Kota Malang) - Rani Rahmadani; Rahayu Puji Suci; Zulkifli Zulkifli (Master Manajemen, 2024)
This study aims to empirically test the influence of brand ambassadors and brand awareness on purchasing decisions moderated by brand image on Le Minerale consumers at Indomaret Soekarno Hatta, Malang City. This study uses a quantitative method with a descriptive approach. Primary data was obtained from 98 respondents. Data analysis used path analysis with the help of SPSS and Smartt-PLS software version 3. The results of this study indicate that (1) brand ambassadors do not influence purchasing decisions: (2) brand awareness influences purchasing decisions (3) brand image does not play a role in moderating the relationship between brand ambassadors and purchasing decisions: (4) brand image does not play a role in moderating the relationship between brand ambassadors and purchasing decisions.